Understanding the Quality of Subject–Object Interaction: A Disciplinary Model for Design Validation. (2nd January 2017) - Sylleros, Alvaro; de la Cuadra, Patricio; Cádiz, Rodrigo F.
Abstract: A disciplinary model is proposed for design validation (DV), which contemplates validation as a process that uses quantitative and qualitative evidence to confirm that products, services, or other objects have enough interaction quality to create a valuable satisfaction level. Our model is based in the subject–object interaction event in order to analyse perceived value. We conceptualize quality as an emergent property from that interaction event, when there is a flowing process between personal meaning and value, projected on the object. This is an advantageous point of view to understand how much, why and in what way designed objects are invested with value, in order to carry out strategic decisions.